2009
DOI: 10.4103/0972-124x.60234
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome and periodontal disease

Abstract: It is important for a dentist to be well informed and updated on the latest research on the association of oral and systemic health. Of late, the metabolic syndrome has gained importance in dental literature, and metabolic syndrome and periodontal disease have been linked. Metabolic syndrome (MeS) is a group of three or more (up to five) interrelated metabolic abnormalities, which increases the risk of cardiovascular morbidity and mortality. Also, both MeS and periodontal disease may be linked through a common… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Chronic periodontitis is one of the most common infectious diseases in humans and can considerably impact systemic health . Earlier studies showed that plaques can significantly contribute to periodontal disease , and that complete removal or control of plaques can greatly reduce the extent of periodontitis .…”
mentioning
confidence: 99%
“…Chronic periodontitis is one of the most common infectious diseases in humans and can considerably impact systemic health . Earlier studies showed that plaques can significantly contribute to periodontal disease , and that complete removal or control of plaques can greatly reduce the extent of periodontitis .…”
mentioning
confidence: 99%
“…Other factors like age, gender, ethnicity, diet, physical activity and various unknown genetic factors contribute to the aetiopathogenesis. [16] Proinflammatory cytokines may be a multidirectional link among periodontitis, obesity and other chronic diseases. [17] High dietary intake and low exercise causes imbalance between energy intake and energy expenditure leading to increased waist circumference.…”
Section: Pathogenesis Of Metabolic Syndromementioning
confidence: 99%
“…The prime emphasis in individuals with metabolic syndrome is to mitigate the underlying risk factors through life style changes . [47] .ATP recommended that obesity be the primary target of intervention for metabolic syndrome.First line of therapy should be weight reduction with increased physical activity.Weight loss lowers serum cholesterol and triglycerides,raises HDL cholesterol,lowers blood pressure and glucose and reduces insulin resistance.In people for whom life style changes is not enough, drug therapy may be required. It is necessary to treat individual components of metabolic syndrome in order to reduce the individual risk associated with each component.…”
Section: Managementmentioning
confidence: 99%